Expression of Stress-Induced Genes in Bronchoalveolar Lavage Cells and Lung Fibroblasts from Healthy and COPD Subjects - Garcia-Ryde, Martin; van der Burg, Nicole M. D.; Berlin, Frida; Westergren-Thorsson, Gunilla; Bjermer, Leif; Ankerst, Jaro; Larsson-Callerfelt, Anna-Karin; Andersson, Cecilia K.; Tufvesson, Ellen (International journal of molecular sciences, 2024)
Chronic obstructive pulmonary disease (COPD) is commonly caused from smoking cigarettes that induce biological stress responses. Previously we found disorganized endoplasmic reticulum (ER) in fibroblasts from COPD with different responses to chemical stressors compared to healthy subjects. Here, we aimed to investigate differences in stress-related gene expressions within lung cells from COPD and healthy subjects. Bronchoalveolar lavage (BAL) cells were collected from seven COPD and 35 healthy subjects. Lung fibroblasts were derived from 19 COPD and 24 healthy subjects and exposed to cigarette smoke extract (CSE). Gene and protein expression and cell proliferation were investigated. Compared to healthy subjects, we found lower gene expression of CHOP in lung fibroblasts from COPD subjects. Exposure to CSE caused inhibition of lung fibroblast proliferation in both groups, though the changes in ER stress-related gene expressions (ATF6, IRE1, PERK, ATF4, CHOP, BCL2L1) and genes relating to proteasomal subunits mostly occurred in healthy lung fibroblasts. No differences were found in BAL cells. In this study, we have found that lung fibroblasts from COPD subjects have an atypical ER stress gene response to CSE, particularly in genes related to apoptosis. This difference in response to CSE may be a contributing factor to COPD progression.